Hajj Regsitration Information Systems Based On Mobile Using Quota Base Method - Siregar, Mhd Alwi Nazri; alda, Muhamad (UIN Sumatera Utara, 2023)
The Office of the Ministry of Religious Affairs of Medan City is a state ministry that provides hajj departure services for prospective pilgrims. In conducting the registration process for Hajj departure, the Office of the Ministry of Religious Affairs of Medan City has not provided a system, so the registration process is still carried out conventionally. Prospective pilgrims must come directly to register for Hajj by filling out the registration form and bringing the requirements needed for registration. By doing this, there are still problems that occur, especially in terms of time, cost, and energy spent. Therefore, the purpose of this research is to build a mobile-based information system using a quota-based method to facilitate Hajj registration. The system development method used is the Rapid Application Development (RAD) method, which consists of planning, design, and implementation workshops. While the tools used by the author in creating a visual information system design are UML (Unified Modeling Language), this mobile-based information system was built using the Kodular framework and the Airtable database. With this information system, it is expected to help prospective pilgrims register for Hajj easily and quickly through Android mobile.